Precisely Tuning Band Gaps of Hexabenzocoronene‐Based MOFs Toward Enhanced Photocatalysis - Zhang, Hao; Li, Cha; Lang, Feifan; Li, Mei; Liu, Haoyu; Zhong, Di‐Chang; Qin, Jun‐Sheng; Di, Zhengyi; Wang, Dan‐Hong; Zeng, Le; Pang, Jiandong; Bu, Xian‐He (Angewandte Chemie International Edition, 2025)
Precise adjusting the band gaps in metal–organic frameworks (MOFs) is crucial for improving their visible‐light absorption capacity during photocatalysis, presenting both a formidable challenge and a charming opportunity. This present study employed a symmetry‐reduction strategy to pre‐design six novel 4‐connected ligands with systematic substituents (−NO2, ‐H, ‐tBu, ‐OCH3, ‐OH and ‐NH2) and synthesized the corresponding pillared‐layer Zr‐MOFs (NKM‐668) retaining the hexaphenylbenzene fragment. Subsequently, the NKM‐668 MOFs were transformed into large‐π‐conjugated hexabenzocoronene‐based MOFs (pNKM‐668) via the Scholl reaction. These twelve MOFs exhibited broad and tunable band gaps over 1.41 eV (ranging from 3.25 eV to 1.84 eV), and the photocatalytic CO2 conversion rate raised by 33.2‐fold. This study not only enriches the type of hexaphenylbenzene‐based MOFs, but also paves the way for nanographene‐containing MOFs in the further application of photocatalysis. This research is the first example to introduce systematic substituents and large conjugated aromatic structure (13 benzene rings) into a long‐range ordered framework simultaneously and achieved directionally modification of nanographene‐containing MOFs. These twelve MOFs exhibited broad and tunable band gaps over 1.41 eV (ranging from 3.25 eV to 1.84 eV), and the photocatalytic CO2 conversion rate raised by 33.2‐fold.